1999
DOI: 10.1098/rspa.1999.0473
|View full text |Cite
|
Sign up to set email alerts
|

On the interfacial properties of micrometre–sized water droplets in crude oil

Abstract: The remarkable stability of water-in-crude oil emulsions is due to the presence of a complex adsorbed layer at the surfaces of the dispersed droplets. Except for its role as a steric barrier, little is known about the in situ properties of this interfacial structure. In this study, new insights into the adsorbed layer are provided by direct micrometre-scale measurements. At low crude content in the bulk where, according to interfacial tension isotherms, there should be little or no surfactants on the droplet s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 28 publications
7
115
1
Order By: Relevance
“…These effects became more severe over time. After the water and oil phases had been in contact for some time, film drainage would become negligible and the interfaces would appear more like the protective skins that have been observed in other studies (42,43). Normally the protective skin would appear after more than an hour of contact between the water and oil phases, although the protective skin would appear within a few minutes for more dilute asphaltene solutions.…”
Section: Formation Of Rigid Interfacesmentioning
confidence: 74%
“…These effects became more severe over time. After the water and oil phases had been in contact for some time, film drainage would become negligible and the interfaces would appear more like the protective skins that have been observed in other studies (42,43). Normally the protective skin would appear after more than an hour of contact between the water and oil phases, although the protective skin would appear within a few minutes for more dilute asphaltene solutions.…”
Section: Formation Of Rigid Interfacesmentioning
confidence: 74%
“…Formation of a stable asphaltene protective film at the oil/water interface has been observed by using the micropipet technique. 15,61,62 The MD simulations clearly showed that the asphaltene molecules could well selfassemble to form ordered graphite-like aggregates in vacuum or at the vacuum/liquid and liquid/liquid interface (Figures 2−4). The asphaltene nanoaggregate generally consists of a few molecules, with the molecular PAHs face-to-face stacking together.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…The recently developed micropipette technique under the NSERC Industrial Researc h Chair in Oil Sands Engineering at the University of Alberta (Moran et al, 1999;2000a,b;Moran 2001;Yeung et al, 1999Yeung et al, , 2000a) is one of the breakthroughs in measuring interf a c i a l properties of very viscous fluids such as bitumen. Application of advances in the measurement of zeta potential distributions of mixtures has made it possible to indirectly detect the heterocoagulation phenomena of fine solids with bitumen (Liu et al, 2002a,b;Xu et al, 2003a).…”
mentioning
confidence: 99%